Trauma Surgery - Karcioglu, Ozgur; Topacoglu, Hakan (IntechOpen, 2018)
Although trauma victims constitute around one-tenth to one-eighth of the total patient volume in hospital emergency departments, the burden of trauma on humankind is beyond these statistics. The twenty-first century is witnessing a growing threat on human beings imposed by many sources, namely natural disasters, terrorism and other conflicts, warfare, and transportation accidents; all of which ignite the rise of major trauma incidents worldwide. Physicians, therefore, get involved in trauma management more and more frequently in time. They need to evaluate, diagnose, treat, and stabilize victims and help them take part in active and productive life as soon as possible. Technological advances have provided many techniques to augment trauma care and resuscitation, fracture healing, wound care, casts and splints, sutures, and transfusions. However, the successful management of trauma warrants a collaboration of emergency medicine, surgical disciplines, intensive care medicine, and almost all the resources of a hospital. This work is an example of a multidisciplinary approach that is a must to maximize synergistic efforts to deliver contemporary care for trauma victims of all ages throughout the world.